Sustainability and nutritional composition of food offer and choices in three hospital canteens in Italy - Diana Menis; Federica Fiori; Peter Cautero; Daniela Zago; Yvonne Beorchia; Lorenzo Dallan; Pietro Vettorazzo; Lucia Lesa; Alessandro Conte; Enrico Scarpis; Laura Brunelli; Maria Parpinel (Heliyon)
Diet is considered one of the most important determinants of health and at the same time a cause of climate change. We conducted a cross-sectional study in three Italian hospital canteens on five consecutive working days to investigate food offer availability and user choices in terms of nutritional intake and environmental impact. Photos of lunch trays were collected by the researchers and food offer and choices were analysed using the Italian Food Composition Database for Epidemiological Studies and the SU-EATABLE LIFE dataset. A total of 1227 lunch meals were analysed. The median energy intake ranged from 646 to 900 kcal/tray. The median energy content from lipids ranged from 32 to 40 % of energy and exceeded that from carbohydrates in one canteen. The median carbon and water footprint ranged from 773 to 1338 g CO2 eq./tray and from 847 to 1229 L H2O/tray, respectively. Differences occurred depending on sex and typology of work. In conclusion, regardless of the differences in the number of food options offered in the three canteens, the choices tended to be suboptimal from a nutritional perspective. The most sustainable choices were made in the canteen without beef on offer. Measures should be taken to increase the variety of vegan and vegetarian options on offer and to improve food choices in terms of nutritional composition and environmental sustainability. This could be done through educational programmes focused on increasing awareness on their diet, and practical indications on how to compose a complete and low impact meal.